Water Safety and Hygienic Practices of Formal and Informal Food Outlets in Malawi - Shadreck Kachembwe Phiri; Ronald Chibwe (European Scientific Journal, ESJ, 2025)
Access to potable water is one of the most important aspects of ensuring consumer safety in food production. Interventions to improve the quality of drinking water and ensuring hygienic practices provide significant benefits to health. However, the monitoring of water quality and maintaining good hygiene remains a challenge in public food outlets where contamination of water may cause the outbreak of disease. The study aimed at assessing the water safety and hygienic practices of formal and informal food outlets in Malawi Community-based cross-sectional study design was conducted in Nkhotakota district, Malawi. A stratified random sampling technique was adopted to select 384 participating food outlets to assess water safety and hygiene practices. Data were collected through interviews and observational checklists. The study revealed that 31% (n = 384) of the food outlets had poor hygienic practices and half of the food handlers in the food outlets (50%, n = 376) had no knowledge of water contaminations. Furthermore, it was found that 96.6% of the food outlets (n = 384) use untreated water. Based on the findings, it was concluded that water being used was not safe for drinking due to poor hygiene and lack of knowledge by food handlers. Due to poor hygiene and lack of knowledge by food handlers, the study recommends widening the scope of policies in food outlets to provide special periodic orientation sessions to food handlers on sanitation and hygiene followed by evaluation in their respective food outlets. Food outlet owners should take responsibility for ensuring that hygienic conditions are followed at their business premises.